FAKTOR YANG MEMENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Elisabeth Tri Aryanti Istimawani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain the empirical evidence about factors which influence dividen policy. The independent variables in this research are firm life cycle, free cash flow, profitability, firm size, asset growth ratio, market to book ratio, firm leverage, managerial ownership, business risk, and the dependent variable is dividend policy. Sample in this research are non financial companies listed in Indonesia Stock Exchange from 2012-2014. The selection of samples used purposive sampling method and there are 87 companies and 261 observations meet those criteria for samples. This research is analyzed using multiple regression analysis. The result of this research show that operating firm size and asset growth ratio have influence to dividend policy. Whereas, firm life cycle, free cash flow, profitability, market to book ratio, firm leverage, managerial ownership, and business risk, over have not influence to dividend policy